Fermentation medium optimization of Streptomyces sp. as an antifungal agent against the Ganoderma boninensis pathogen in oil palm - Syamsika Tahir; Widya Dwi Rukmi Putri; Agustin Krisna Wardani; Rofiq Sunaryanto (Universitas Gadjah Mada, 2023)
Ganoderma boninensis is the most common fungus which attacks oil palm trees. However, a significant percentage of inhibition to the problem is found through the use of Streptomyces sp. The optimization of the Streptomyces sp. fermentation medium growth factors affects the secondary metabolites production. This study aimed to identify the best formulation of carbon and nitrogen sources and the optimum concentration of Streptomyces sp. fermentation medium for antifungal compound production. The results showed that the best sources of carbon and nitrogen were liquid glucose and monosodium glutamate in the inhibition zones of 16.7 mm and 6.3 mm, while the best concentration levels were 20 g/L and 14.19 g/L, respectively. The results of the first optimization showed an inhibition zone response and area (%) of the optimum high‐performance liquid chromatography (HPLC) chromatogram of 24.39 mm and 62.68 percent, respectively. Taking the suggestion of the first optimization, the second optimization produced 15.2 g/L and 8.3 g/L. The predicted value of the inhibition zone was 21.47 mm, and the area (%) of the HPLC chromatogram was 53.44 percent. The validation results showed an inhibition zone response of 22.01 mm and an HPLC chromatogram area (%) of 54.86 percent. The difference between the predicted and validation values was less than 5 percent; the validation value was thus in line with the value predicted by Design Expert 10.0.7. The chemical formula of the probable active compound is that of the cyclo(phenylalanyl‐prolyl) compound.